2003
DOI: 10.1121/1.1538247
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical evidence for auditory compression at low characteristic frequencies

Abstract: Psychophysical estimates of compression often assume that the basilar-membrane response to frequencies well below characteristic frequency (CF) is linear. Two techniques for estimating compression are described here that do not depend on this assumption at low CFs. In experiment 1, growth of forward masking was measured for both on- and off-frequency pure-tone maskers for pure-tone signals at 250, 500, and 4000 Hz. The on- and off-frequency masking functions at 250 and 500 Hz were just as shallow as the on-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
63
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 42 publications
(55 reference statements)
23
63
2
Order By: Relevance
“…7). An emergent property of the present model is that it accounts for the broad bandwidth of compression at 500 Hz reported elsewhere Lopez-Poveda et al 2003;Plack and Drga 2003).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…7). An emergent property of the present model is that it accounts for the broad bandwidth of compression at 500 Hz reported elsewhere Lopez-Poveda et al 2003;Plack and Drga 2003).…”
Section: Discussionmentioning
confidence: 68%
“…This is particularly true at low frequencies, where compression and hence active cochlear mechanisms occur for a comparatively broader range of stimulus frequencies than at high frequencies Lopez-Poveda et al 2003;Plack and Drga 2003). Here, a physiologically inspired, phenomenological computer model of forward masking with efferent control is used to explain the effects of contralateral stimulation on PTCs.…”
Section: Introductionmentioning
confidence: 99%
“…reported in previous studies using the temporal window model (e.g., Plack and Oxenham 1998;Oxenham and Plack 2000;Plack and Drga 2003). The final predictor was the frequency of the offfrequency masker (f m ), which indirectly simulated a change in the slope of the linear reference by applying more active processing to the offfrequency masker.…”
Section: Methodsmentioning
confidence: 99%
“…In general, for a given absolute value of C, harmonic tone complexes with positive phase curvatures (i.e., C>0) produce less masking than complexes with the corresponding negative phase curvatures in both simultaneous masking (e.g., Smith et al 1986;Kohlrausch and Sander 1995;Lentz and Leek 2001;Oxenham and Dau 2001a, b) and forward masking (Carlyon and Datta 1997a), in line with expectations, based on the negative phase curvature of the cochlear filters. For stimuli with positive phase curvature, the negative phase curvature of the auditory filters counteracts that of the stimulus to produce a filtered waveform with less phase curvature (i.e., near-constant group delay across frequency) and a highly modulated temporal envelope at the output of the cochlear filter tuned to the CF, as illustrated in Figure 1 and demonstrated physiologically (Recio and Rhode 2000;Summers et al 2003). In simultaneous masking, temporal modulations in the masker envelope lead to low-energy epochs in the masker, which make the signal more detectable.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of psychophysical masking, it seems that the temporal waveshape after cochlear filtering determines the amount of masking. Physiological studies in mammals have shown that the phase curvature of the cochlear filters, measured on the basilar membrane (BM) and in the auditory nerve, is approximately constant and negative for frequencies around the characteristic frequency (CF), at least for CFs greater than about 1 kHz Carney et al 1999;Recio and Rhode 2000). Psychophysical estimates of the phase curvature of the auditory filters have used harmonic complexes with the phases of components set according to a variant of Schroeder's (1970) equation, provided by Lentz and Leek (2001):…”
Section: Introductionmentioning
confidence: 99%